1976
DOI: 10.1042/cs0500001
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Circulating Lactate Dehydrogenase-5 in the Rabbit

Abstract: 1.In an attempt to determine the mechanism whereby enzymes are removed from the circulating plasma, purified rabbit-muscle lactate dehydrogenase-5 was labelled with lz5I and injected intravenously into rabbits. During the first hour after injection enzyme activity and radioactivity disappeared from the plasma at comparable fast rates, which are attributed mainly to distribution of the enzyme throughout the extracellular fluid. This was followed by a phase lasting about 7 h during which enzyme activity disappea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Radioactivity of spleen was corrected for the contaminating blood using the value (47 p1 of plasma per gm of spleen tissue) (27). Radioactivity of kidneys was also corrected for blood contribution by measuring hemoglobin concentration in the homogenate as described (28). Radioactivity was det.ermined in a Packard Autogamma scint,illation spectrometer Model 5130.…”
Section: Determination Of Tissue Distribution Ofmentioning
confidence: 99%
“…Radioactivity of spleen was corrected for the contaminating blood using the value (47 p1 of plasma per gm of spleen tissue) (27). Radioactivity of kidneys was also corrected for blood contribution by measuring hemoglobin concentration in the homogenate as described (28). Radioactivity was det.ermined in a Packard Autogamma scint,illation spectrometer Model 5130.…”
Section: Determination Of Tissue Distribution Ofmentioning
confidence: 99%
“…Knowledge of this latter process has advanced less rapidly than that relating to entry of enzymes into the circulation, but recent research suggests that the process of inactivation begins in the bloodstream [12].…”
Section: Production and Release Of Enzymes By Cellsmentioning
confidence: 99%
“…In the rabbit it was shown that lactate dehydrogenase-5 (EC 1.1.1.27) activity was lost from the circulation at a faster rate than the radioactivity of "'1-labelled enzyme (Qureshi & Wilkinson, 1976). However, such findings give no information about the mechanism of enzyme catabolism except that the initial stages do occur in the intravascular compartment.…”
Section: Introductionmentioning
confidence: 99%